Mindfulness – seeping through the cracks in the American context of teacher education. (2nd January 2018) - Powietrzyńska, Małgorzata; Noble, Linda
ABSTRACT: In the context of the United States, we provide our rationale for infusing mindfulness-based interventions (MBIs) into a graduate-level teacher education course. In our philosophy and pedagogical approach we attempt to counterbalance an individualistic, divisive, oppressive, and often dehumanising nature of education. Adopting Richard Davidson's wellness framework, we describe how our use of MBIs, including breathing meditation, heuristics, free-writing, and cogenerative dialogues, may contribute to cultivating components of integrated teacher well-being. Mindfulness is framed as a relational construct and as a part of a toolkit which educators may access in their professional and personal lives. Drawing on data obtained through an end-of-semester feedback survey, we provide a brief analysis of students' perceptions of the value of mindfulness practices in teacher preparation and beyond.